Acoustic stimulation increases implicit adaptation in sensorimotor adaptation. (28th June 2021) - Leow, Li‐Ann; Tresilian, James R.; Uchida, Aya; Koester, Dirk; Spingler, Tamara; Riek, Stephan; Marinovic, Welber
Abstract: Sensorimotor adaptation is an important part of our ability to perform novel motor tasks (i.e., learning of motor skills). Efforts to improve adaptation in healthy and clinical patients using non‐invasive brain stimulation methods have been hindered by inter‐individual and intra‐individual variability in brain susceptibility to stimulation. Here, we explore unpredictable loud acoustic stimulation as an alternative method of modulating brain excitability to improve sensorimotor adaptation. In two experiments, participants moved a cursor towards targets, and adapted to a 30º rotation of cursor feedback, either with or without unpredictable acoustic stimulation. Acoustic stimulation improved initial adaptation to sensory prediction errors in Study 1, and improved overnight retention of adaptation in Study 2. Unpredictable loud acoustic stimulation might thus be a potent method of modulating sensorimotor adaptation in healthy adults.